Seismic ground response at Lotung: Hysteretic elasto-plastic-based 3D analyses. Issue 85 (June 2016) - Amorosi, A.; Boldini, D.; di Lernia, A.
Abstract: This paper presents a non-linear finite element study to back-interpret the free field seismic response recorded at the Lotung Large-Scale Seismic Test site. The study is carried out in the time domain by the Finite Element (FE) code PLAXIS 3D, considering the vertical wave propagation of both the horizontal components of motion. The non-linear soil behaviour is simulated through a constitutive model, the Hardening Soil model with Small-Strain Stiffness ( HSsmall ), capable of describing the cyclic response of the material at different strain levels. In the paper, the constitutive response of the HSsmall model is firstly investigated through numerical simulations of strain-controlled cyclic shear tests under single and multi-directional conditions at low strain levels. Then, it is adopted to back-analyse the recorded free field seismic response, comparing the FE numerical results to the in-situ down-hole and surface signals recorded during two earthquakes occurred on May 20th and July 17th 1986, characterized by different peak ground accelerations. Highlights: Soil nonlinearity is described by an isotropic hardening elasto-plastic model. Multi-directionality of shearing conditions on constitutive response is investigated. The free field response recorded at LSST site is studied by a 3D FE model. The ground response predicted by the model well agrees with the monitoring data. The seismic response is slightly over-predicted under multi-directional conditions.